Validação de metodologia analítica para análise de solventes residuais na matéria prima indapamida por cromatografia gasosa - Fiorentin, Anderson Luiz (2021)
Solvents are chemical reagents used within the synthesis process of IFA (active pharmaceutical input), however, after the withdrawal processes, part of these reagents may remain in the formed IFA. Due to their toxicity, it is necessary to assess whether the residual quantity follows the concentration specifications imposed by ICH (International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use). These specifications were obtained by studies and tests stating the limit concentration for human consumption without causing damage to health. Thus, this study aims to validate an analytical methodology for the control of residual solvents ethanol, 2-propanol, chloroform and tetrahydrofuran (THF) using the gas chromatography technique with "transferline" injection and FID detector ("Flame Ionization Detector") in the raw material of Indomatography. To carry out the control of these substances it was necessary to validate the analytical methodology using the experiments imposed by the regulatory body to ANVISA (National Health Surveillance Agency), the evaluated tests are described in resolution DRC 166 of July 24 of 2017.O selectivity test showed that the presence of solvents together does not interfere in the quantification of the same individually, obtaining a chromatogram with well resolved peaks. All solvents analyzed presented linear data of the Pearson correlation coefficient (r) greater than 0.99, these values were calculated for the linear concentration range studied, with values starting from 40% up to 240%, within this range 7 levels and 3 curves were evaluated for the 4 solvents. The accuracy results were evaluated in 3 ranges: 40% (low point), 120% (midpoint) and 240% (high point), showing a variation from 97 to 105% in the recovery values for the 4 solvents. All solvents showed good repeatability and reproducibility, with DPR (Relative Standard Deviation) values of less than 5.3%. The highest DPR values belong to the chloroform, due to its concentration of work being lower (60 ppm) reflecting its specification according to the ICH, which determines which concentration is safe to the health of the patients. For the robustness test, the methodology was robust for initial ramp changes of the furnace, column mark and stream range of the plough gas 3.8 mL.min-1 up to 4.0 mL.min-1, however did not present good robustness for the drag gas flow range greater than 4.0 mL.min-1 up to 4.2 mL.min-1. It is possible to prove by the results that the methodology has proved precise, accurate and linear, proving the validation of the methodology and consequently its use as solvent control method in the raw material of IFA Indapamida.